P155 ELUCIDATING INTERACTIONS BETWEEN THE IMMUNE SYSTEM AND THE GUT MICROBIOTA IN A REDUCTIONIST MURINE MODEL OF INFLAMMATORY BOWEL DISEASE. (7th February 2019) - Tsou, Amy; Goettel, Jeremy; Biswas, Amlan; Kang, Yu Hui; Saltzman, Jeffrey; Kelly, Ryan; Gringauz, Jordan; Shen, Zeli; Fox, James; Horwitz, Bruce; Snapper, Scott
Abstract: Background: Patients with inflammatory bowel disease (IBD) have altered intestinal microbial composition, but whether this altered microbiota is a cause or consequence of inflammation is unclear. The importance of the gut microbiota in IBD pathogenesis has been shown in many murine models, since colitis fails to develop in genetically-susceptible mice when re-derived into germ-free environments. Wiskott-Aldrich syndrome protein (WASP)-deficient (Was -/- ) mice exhibit immune dysregulation and develop IBD, similar to human patients with mutations in WAS. The colitis that develops in Was -/- mice is Helicobacter-dependent, but the presence of other commensal bacteria is also required. We have developed a reductionist model to study the role of the microbiota in intestinal inflammation by colonizing Was -/- mice with Helicobacter and altered Schaedler flora (ASF), a defined group of 8 commensal bacteria. We have previously shown that addition of Helicobacter to ASF in Was -/- mice, but not WT mice, drastically changes the microbial community structure and supports the development of intestinal inflammation. The goal of this study was to clarify the temporal relationship between onset of inflammation and shifts in gut microbial community structure. Methods: We colonized germ-free WT, heterozygous, and Was -/- mice with ASF and Helicobacter hepaticus. Fecal samples were collected longitudinally for 16S rRNA sequencing and measurement of fecal lipocalin-2 (Lcn-2) by ELISA. Results: Although all mice were gavaged with Helicobacter on day 0, 16S rRNA sequencing of the stool showed that Helicobacter only colonized stably in a subset of the mice. Of the mice with successful Helicobacter colonization, Was -/- mice were colonized with higher levels of Helicobacter and lower levels of Mucispirillum compared to WT and heterozygous mice. Preliminary results show that this was associated with increased inflammation, as measured by Lcn-2. The divergence of Helicobacter and Mucispirillum abundance by genotype occurred prior to the divergence in Lcn-2. Conclusions: Our results show that the immune system plays an important role in shaping the intestinal microbiota, since the relative abundances of Helicobacter and Mucispirillum differed in Was -/- compared to WT and heterozygous mice. These differences preceded the onset of inflammation, suggesting that they may contribute to the development of colitis. Thus, this study indicates that there is a bidirectional relationship between the immune system and the gut microbiota.